FPGA Architecture Optimization Using Geometric Programming - Smith,AM; Constantinides,GA; Cheung,PYK (IEEE Transactions on Computer-Aided Design of Integrated Circuits and Systems, 2010)
This paper is concerned with the application of geometric programming to the design of homogeneous field programmable gate array (FPGA) architectures. The paper builds on an increasing body of work concerned with modeling reconfigurable architectures, and presents a full area and delay model of an FPGA. We use a geometric programming framework to show how transistor sizing and high-level architecture parameter selection can now be solved as a concurrent optimization problem. We validate the model through the use of simulation program with integrated circuit emphasis (SPICE) models and the versatile place and route (VPR) FPGA architecture simulation tool. Not only does the optimization framework allow architectures to be optimized orders of magnitude faster than previous work, but the combined optimization can lead to different architectural conclusions compared to conventional methods by exploring the coupling between the two sets of optimization variables. Specifically, we show that as delay takes more significance in the objective of the optimization, there should be more lookup tables in a logic block, whereas conventional techniques suggest that there should be fewer lookup tables in an FPGA logic block.